2007
DOI: 10.1103/physrevb.75.104404
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization reversal in orthovanadateRVO3compounds (R=La, Nd, Sm, Gd, Er, and Y): Inhomogeneit

Abstract: Abstract:We report on a study of various RVO 3 single-crystal samples (R = La, Nd, Sm, Gd, Er and Y) which show temperature-induced magnetization reversal. For compounds with lighter rare-earths (R = La, Nd and Sm), magnetization reversal can be observed for magnetic field applied in the ab plane and along the c axis, whereas for the heavy rare-earths (R = Gd, Er) magnetization reversal is only observed when the field is applied along the a axis. YVO 3 has a magnetization reversal along all the main crystallog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 39 publications
(103 reference statements)
3
54
0
Order By: Relevance
“…A single‐crystalline boule of 6 mm in diameter and 60–70 mm in length was then grown by the traveling solvent floating zone method. The crystallinity of the boule was checked by X‐ray analysis and the composition by the electron probe microanalysis …”
Section: Methodsmentioning
confidence: 99%
“…A single‐crystalline boule of 6 mm in diameter and 60–70 mm in length was then grown by the traveling solvent floating zone method. The crystallinity of the boule was checked by X‐ray analysis and the composition by the electron probe microanalysis …”
Section: Methodsmentioning
confidence: 99%
“…The orientation of the V spins within the C-SO phase has not been reported for all members of the series and its dependence on the rare earth is still rather unclear. 18 Available evidence provided by magnetization and neutron-diffraction measurements suggests that the V spins lie in the bc plane for RVO 3 with small rare earths 17,19 and in the ab plane for larger rare earths 16,20 but it should be noted that the ab-plane configuration is forbidden by symmetry arguments. 16,17 These two regions of the magnetic RVO 3 phase diagram coincide approximately with those defined by the G-OO phase monoclinic angle.…”
Section: A Critical Phenomenamentioning
confidence: 99%
“…This phase separation is therefore possibly common to Tb, Gd, Eu, and Sm members of the RVO 3 series due to their similar, middle rare-earth radius. Furthermore, Tung et al 7 commented that the phase separation is consistent with, but not equivalent to, their model of MR based upon the existence of random field spins. However, in a neutron diffraction study, 14 no phase separation was observed in single-crystal TbVO 3 .…”
Section: Introductionmentioning
confidence: 96%
“…5 In this paper we focus on the R = Sm member of the series belonging to the third subgroup outlined above. In SmVO 3 , heat capacity measurements show T OO = 192.6 K and T N = 130 K. 7 The majority of RVO 3 compounds (excluding R = Pr, Ce, Lu) exhibit magnetization reversal (MR). Upon cooling SmVO 3 below T N , the magnetization, which is initially positive, smoothly reverses twice at T = 127.5 and 63.8 K. 7 A number of mechanisms for the MR have been proposed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation